2006
DOI: 10.1038/modpathol.3800538
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alterations in columnar cell lesions of the breast

Abstract: Columnar cell lesions of the breast include a morphologic spectrum of simple columnar cell change, columnar cell hyperplasia, columnar cell hyperplasia with atypia and ductal carcinoma in situ of micropapillary/cribriform type. Invasive carcinomas of low grade are often seen in association with this spectrum. The biologic significance of these lesions that are commonly found on breast biopsies is unknown. Three cases of formalinfixed, paraffin-embedded breast tissues, each displaying the entire spectrum of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
1
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 22 publications
2
71
1
8
Order By: Relevance
“…[22][23][24][25][26][27][28] Previously, Moinfar et al 22 analyzed loss of heterozygosity in Ductal Intraepithelial Neoplasiaflat lesions, and found significant alterations, including changes in common with concurrent carcinoma; however, 9 of the 22 studied cases were 'pleomorphic' Ductal Intraepithelial Neoplasia-flat, equivalent to clinging carcinoma (high nuclear grade flat ductal carcinoma in situ). In a subsequent study using array comparative genomic hybridization Moinfar's group showed by that Ductal Intraepithelial Neoplasia low grade harbored changes common to lobular neoplasia, low nuclear grade ductal carcinoma in situ, and invasive carcinoma (loss of 16q, gain of 1q).…”
Section: Pik3ca Mutations In Columnar Cell Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28] Previously, Moinfar et al 22 analyzed loss of heterozygosity in Ductal Intraepithelial Neoplasiaflat lesions, and found significant alterations, including changes in common with concurrent carcinoma; however, 9 of the 22 studied cases were 'pleomorphic' Ductal Intraepithelial Neoplasia-flat, equivalent to clinging carcinoma (high nuclear grade flat ductal carcinoma in situ). In a subsequent study using array comparative genomic hybridization Moinfar's group showed by that Ductal Intraepithelial Neoplasia low grade harbored changes common to lobular neoplasia, low nuclear grade ductal carcinoma in situ, and invasive carcinoma (loss of 16q, gain of 1q).…”
Section: Pik3ca Mutations In Columnar Cell Lesionsmentioning
confidence: 99%
“…Recent loss of heterozygosity, comparative genomic hybridization, and immunohistochemical studies have suggested that columnar cell lesions, might represent the 'missing link' in low-grade breast cancer progression, as the earliest identifiable non-obligate precursor. 18,[22][23][24][25][26][27][28] In order to further address the pathogenetics of columnar cell lesions, we screened a cohort of columnar cell lesions, most with matched normal breast tissue and/or concurrent carcinoma, for a large panel of known activating point mutations, including PIK3CA and AKT1 mutations.…”
mentioning
confidence: 99%
“…For a description of the reasons at the basis of assumptions (1)- (5) see [36][37][38]. The RIEDP takes the form:…”
Section: Rate Of Internal Entropy Density Production For Glucose Catamentioning
confidence: 99%
“…8 Many studies have shown that there is an association between the presence of columnar cell lesions and ductal carcinoma in situ, atypical ductal hyperplasia or lobular neoplasia, and low-grade luminal type invasive carcinomas like tubular and lobular carcinomas. 2,4,[9][10][11][12][13][14][15] Moreover, protein expression as detected by immunohistochemistry is quite similar between columnar cell lesions and atypical ductal hyperplasia or ductal carcinoma in situ grade I. 8,15,16 Also, molecular studies provide evidence that atypical columnar cell lesions may be the 'missing link' between normal breast tissue and low-grade ductal carcinoma in situ and/or low-grade invasive carcinomas, 9,10,15,17,18 thereby being true precursors.…”
mentioning
confidence: 99%